Cytoplasmic [Ca2+] and intracellular pH in lymphocytes. Role of membrane potential and volume-activated Na+/H+ exchange (The Rockefeller University Press, 1987)
The effect of elevating cytoplasmic Ca2+ [( Ca2+]i) on the intracellular pH (pHi) of thymic lymphocytes was investigated. In Na+- containing media, treatment of the cells with ionomycin, a divalent cation ionophore, induced a moderate cytoplasmic alkalinization. In the presence of amiloride or in Na+-free media, an acidification was observed. This acidification is at least partly due to H+ (equivalent) uptake in response to membrane hyperpolarization since: it was enhanced by pretreatment with conductive protonophores, it could be mimicked by valinomycin, and it was decreased by depolarization with K+ or gramicidin. In addition, activation of metabolic H+ production also contributes to the acidification. The alkalinization is due to Na+/H+ exchange inasmuch as it is Na+ dependent, amiloride sensitive, and accompanied by H+ efflux and net Na+ gain. A shift in the pHi dependence underlies the activation of the antiport. The effect of [Ca2+]i on Na+/H+ exchange was not associated with redistribution of protein kinase C and was also observed in cells previously depleted of this enzyme. Treatment with ionomycin induced significant cell shrinking. Prevention of shrinking largely eliminated the activation of the antiport. Moreover, a comparable shrinking produced by hypertonic media also activated the antiport. It is concluded that stimulation of Na+/H+ exchange by elevation of [Ca2+]i is due, at least in part, to cell shrinking and does not require stimulation of protein kinase C.